Minocycline Preserves the Integrity and Permeability of BBB by Altering the Activity of DKK1–Wnt Signaling in ICH Model. (1st September 2019) - Wang, Guoqing; Li, Zhihua; Li, Shujian; Ren, Junling; Suresh, Vigneyshwar; Xu, Dingkang; Zang, Weidong; Liu, Xianzhi; Li, Wei; Wang, Huizhi; Guo, Fuyou
Abstract: Disruption of the blood–brain barrier (BBB) and subsequent neurological deficits are the most severe consequence of intracerebral hemorrhage (ICH). Minocycline has been wildly used clinically as a neurological protective agent in clinical practice. However, the underlying mechanisms by which minocycline functions remain unclear. Therefore, we assessed the influence of minocycline on BBB structure, neurological function, and inflammatory responses in a collagenase-induced ICH model, and elucidated underlying molecular mechanisms as well. Following a single injection of collagenase VII-S into the basal ganglia, BBB integrity was assessed by Evans blue extravasation while neurological function was assessed using an established neurologic function scoring system. Minocycline treatment significantly alleviated the severity of BBB disruption, brain edema, and neurological deficits in ICH model. Moreover, minocycline decreased the production of inflammatory mediators including TNF, IL-6, and MMP-9, by microglia. Minocycline treatment decreased DKK1 expression but increased Wnt1, β-catenin and Occludin, a phenomenon mimicked by DKK1 silencing. These data suggest that minocycline improves the consequences of ICH by preserving BBB integrity and attenuating neurologic deficits in a DKK1-related manner that involves enhancement of the Wnt1–β-catenin activity. Highlights: Blood–brain barrier disruption can cause severe neurological deficits. Minocycline decreases DKK1 expression and invigorating Wnt–β-catenin activity. Minocycline decreases the production of inflammatory mediators in microglia. Minocycline alleviates BBB disruption and neurological deficits in ICH model.